New and unusual field records of Chelus spp. in Venezuela (Testudines: Chelidae): Registros nuevos e inusuales de Chelus spp. en Venezuela (Testudines: Chelidae) - Escalona, Tibisay (Anartia, 2024)
The genus Chelus, matamata turtles, is native to northern South America, being widely distributed throughout the Amazon and Orinoco Basins. It reaches the largest adult body size among the extant Chelidae, and with straightline carapace length (SCL) ranging from 31.1-40.4 cm (Pritchard & Trebbau 1984). However, larger individuals do exist (i.e., > 50 cm SCL Barrio-Amorós & Manrique 2006). Matamatas are very charismatic and easy to recognize by their unique morphological appearance (i.e., extremely flat and triangular head, long and thick neck, wide mouth, long pointy snout, and a carapace with three dorsal keels). They are classified as “Least Concern” by the IUCN (2021), yet their natural history is largely unknown despite the great interest shown by the herpetological community. Likewise, the distribution range of Chelus species remains only partially verified, and the taxonomic revision of the genus suggesting the recognition of two extant species leaves (see below) the geographic coverage of each of them undocumented. This lack of comprehensive distribution data hampers efforts to accurately understand the biogeography and ecological niches of each species, requiring further research to delineate their ranges more precisely.